2019
DOI: 10.1002/ijgo.12893
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of the prevalence of polycystic ovary syndrome in rural and urban populations

Abstract: Objective: To assess the prevalence and risk factor profile of polycystic ovary syndrome (PCOS) in Haryana, India. Methods:A large-scale cross-sectional study was conducted among women of reproductive age in Haryana between December 2015 and May 2017. A random multi-stage stratified sampling method was adopted. PCOS screening was based on questionnaires.Blood samples for hormonal analysis were collected from those with probable and definitive PCOS cases. Women with menstrual irregularities (MI), hyperandrogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…In our study 12 out of 72 (16.6%) of women with PCOS has metabolic syndrome where as in study by Joshi et al it was 1 out of 135 and in study by Deswal et al it was 6.01% [14,20] . In our study infertility and depression was seen in 73.6% and 65.3% where as in study by Deswal et al it was 18.1% and 61.7% respectively [21] . Although psychosocial problem was the second most common comorbidity in women with PCOS it was least addressed.…”
Section: Discussionsupporting
confidence: 76%
“…In our study 12 out of 72 (16.6%) of women with PCOS has metabolic syndrome where as in study by Joshi et al it was 1 out of 135 and in study by Deswal et al it was 6.01% [14,20] . In our study infertility and depression was seen in 73.6% and 65.3% where as in study by Deswal et al it was 18.1% and 61.7% respectively [21] . Although psychosocial problem was the second most common comorbidity in women with PCOS it was least addressed.…”
Section: Discussionsupporting
confidence: 76%
“…Anovulation/oligoovulation is typified by irregularities in the menstrual cycle caused due to ovulatory impairment, which accounts nearly 70% in PCOS women 41,42 . It has now been well established that the microbiome in the intestinal tract can influence a wide spectrum of physiological functions 43 .…”
Section: Oligo/anovulation and Microbiomementioning
confidence: 99%
“…Anovulation/oligoovulation is typified by irregularities in the menstrual cycle caused due to ovulatory impairment, which accounts nearly 70% in PCOS women. 41,42 It has now been well established that the microbiome in the intestinal tract can influence a wide spectrum of physiological functions. 43 Recent studies have implicated interference between female's gut and vaginal tract microbiota, which are very complex biological ecosystems and are constantly communicating with one another.…”
Section: Oligo/anovulation and Microbiomementioning
confidence: 99%
“…[ 12 ] A large-scale cross-sectional study conducted among women of reproductive age in Haryana, India reported that 94/2400 (4.21%) had PCOS. [ 13 ] A systematic review identified that the pooled mean prevalence of PCOS was 21.27% using multiple diagnostic criteria. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%